Cerebrospinal Fluid C-reactive Protein in the Diagnosis of Meningitis in Children - Soetiman Soetiono; Sunartini Sunartini; Soeroyo Machfudz; Setyawati P. S. (Indonesian Pediatric Society, 1989)
The mortality rate of bacterial meningitis in infants and children is still high (40-50%). Such a mortality rate can be reduced by establishing a prompt and accurate diagnosis. Until now the diagnosis of meningitis is still an important clinical problem.The examination of cerebrospinal fluid C-reactive protein had been done in 44 clinical meningitis patients in the Paediatrics Department, Dr. Sardjito General Hospital qualitatively by means of latex agglutination slide test. Cerebrospinal fluid C-reactive protein was positive in 90% (18120) of bacterial meningitis patients compared to 8.3 % (2124) of non bacterial meningitis patients. The sensivity and specificity of cerebrospinal fluid C-reactive protein were 90% and 91.7% respectively and these value were more sensitive and specific than those of white cell count, absolute polymorphonuclear, glucose and protein levels and the cerebrospinal fluid smear (50-80% and 80-91%, respectively) which had been performed in the diagnosis of meningitis.It can be concluded that the examination of cerebrospinal fluid C-reactive protein can be used as a diagnostic tool of bacterial meningitis.